2019
DOI: 10.21203/rs.2.16026/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification and expression profiling of SET DOMAIN GROUP family in Dendrobium catenatum

Abstract: Background: Dendrobium catenatum used as a precious Chinese herbal medicine is a kind of epiphytic orchid plant which grows on the trunks and cliffs and often faces up to diverse environmental stresses. SET DOMAIN GROUP (SDG) proteins act as histone lysine methyltransferases which are involved in pleiotropic developmental events and stress responses through modifying chromatin structure and regulating gene transcription, but their roles in D. catenatum are unknown. Results: In this study, we identified 44 SDG … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that DcCslDs are involved in plant responses to environmental stresses [55][56][57].…”
Section: Expression Of Dccslds In Response To Drought and Low-temperamentioning
confidence: 99%
“…It has been shown that DcCslDs are involved in plant responses to environmental stresses [55][56][57].…”
Section: Expression Of Dccslds In Response To Drought and Low-temperamentioning
confidence: 99%